The effect of organizational learning on job commitment, job satisfaction and work performance in Malaysia: a mediation analysis - Raja Kasim, Raja Suzana; Ong, Gua Pak; Uli, Jegak
The purpose of this paper is to examine the role of organizational commitment and job satisfaction as mediator on the relationship between organizational learning and public service managers’ work performance. The population of the study is around 4579 Administrative and Diplomatic (ADS) officers working in 28 ministries located in the Federal Territory of Kuala Lumpur and Putrajaya, Malaysia. The collection of primary data was through the distribution of personally administered questionnaires to the respondents who were chosen by systematic sampling procedure. A total of 435 (87%) answered questionnaires were returned and used in the final analysis. The findings indicate organizational learning is equally important in explaining organizational commitment, job satisfaction and work performance. At the same time, organizational learning, job satisfaction and organizational commitment are also equally important in explaining work performance among the public service managers. In conclusion, this paper contributes and enriches present knowledge in this field and it can be argued that western theories can be valid in non-western setting. The implications of the findings of this paper are that top management in ministries need to pay serious attention and effort to create a conducive environment that will encourage learning among the employees. This will improve work outcomes and consequently improve the government delivery system.